Health and environment in the context of urbanization - Takano, Takehito (Springer-Verlag, 2007)
This paper introduces a series of research projects designed to fulfill the societal role of environmental health studies by investigating (1) the dynamic and complex relationships between environmental conditions and (2) health in an urban setting. Research in this first category has revealed the existence of the combined influence of multiple physical environmental factors on health and its mechanisms. In the second category, there have been a number of studies of the integrated influence of social environmental factors on health employing an aggregate modeling of multiple determinants of health and studies of individual topics related to social determinants of health. These research projects have contributed to the formulation of specific remedies and the development of comprehensive health policies. Participatory approaches have been used to enhance capacity building opportunities and to ensure that research results reflect the actual conditions in urban societies. Healthy Cities projects and programs have been developed in close collaboration with this type of research. Urban societies have become interdependent and share the same issues globally. Further research into the relationships between health and the environment in the context of urbanization will expand the base of evidence applicable to the complex realities in modern societies.